Development of new method of preparation of photographic gelatin - E. Yu. Bulychev; V. E. Gaponova; B. I. Shapiro; A. S. Mikhailov (Тонкие химические технологии, 2010)
A new technology of preparation of photographic gelatin was developed on the basis of an accessible homogeneous raw material containing a collagen. Photographic properties of the obtained gelatin were tested.